PENGARUH DIVIDEND PAYOUT RATIO DAN DIVIDEND YIELD TERHADAP HARGA SAHAM PADA INDEKS LQ45 - Bagaskara, Doni; Rohmadi, Rohmadi (Brainy: Jurnal Riset Mahasiswa, 2023)
This research aims to determine the effect of dividend payout ratio and dividend yield on stock prices in the LQ45 Index. This research uses quantitative methods, the research object uses secondary data from 45 companies listed on the LQ45 Index in 2023, this research uses a sample collection technique model with non-probability sampling or non-random sampling. The data source comes from IDX Company LQ45 2023 data and documents on the Indonesia Stock Exchange (BEI). The analysis process uses multiple regression analysis of cross section data assisted by SPSS 2023. The results of this study state that the dividend payout ratio has no effect on stock prices, while the dividend yield has a positive effect on stock prices.